2022
DOI: 10.3389/fnut.2022.965687
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of intestinal microflora by the intake of millet porridge improves gastrointestinal motility

Abstract: Foxtail millet (Setaria italica) has a long history of treating gastrointestinal ailments in China; however, little is known about the functional mechanism driving its therapeutic effects. The primary edible form of millet is porridge. This study investigates the effects of millet porridge on diphenoxylate-induced constipation and intestinal microflora in mice. Fifty mice were randomly divided into five groups: normal control group, constipation model group, and low-dose, medium-dose, and high-dose millet porr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…There are significant differences in the quantity and composition of intestinal microbiota between constipated patients and healthy individuals 29 . Some studies have shown that the relative abundance of Bifidobacterium and Lactobacillus is reduced in constipated patients, while the relative abundance of Bacteroidetes , Fusobacterium , and Enterobacter is enhanced 20 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…There are significant differences in the quantity and composition of intestinal microbiota between constipated patients and healthy individuals 29 . Some studies have shown that the relative abundance of Bifidobacterium and Lactobacillus is reduced in constipated patients, while the relative abundance of Bacteroidetes , Fusobacterium , and Enterobacter is enhanced 20 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the consumption of porridge may be a protective factor for IBD. This may be attributed to the fact that porridge consumption increases gastrointestinal motility and water content in the stool and also enhances the abundance of bene cial gut bacteria such as Bi dobacteria and Lactobacilli, while reducing the abundance of potentially pathogenic bacteria such as Escherichia coli, Enterococcus, and Clostridium [29].…”
Section: Discussionmentioning
confidence: 99%
“…The prebiotics, probiotics, and synbiotics groups were intragastrically administrated 0.3 mL of ST (1.5 g/kg), alive L. sakei (3 × 10 9 CFU/mouse), and the mixture of ST and L. sakei (1.5 g/kg plus3 × 10 9 CFU/mouse), respectively. After 21 days of intervention, all mice were fast for 16 h. On day 22, all mice except the normal mice were intragastrically administrated with diphenoxylate (10 mg/kg) to establish the constipation mouse model according to previous publications ( 31 , 32 ). After 30 min, all mice were gavaged with 0.25 mL of ink.…”
Section: Methodsmentioning
confidence: 99%